Pemberian Pendidikan Kesehatan Penyakit Menular Dan Tidak Menular Pada Anggota TNI AD - Daryaswanti, Putu Intan; Pendet, Ni Made Diah Pusparini; Remiasa, I Wayan (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2026)
Background: Non-communicable diseases (NCDs) are a leading cause of morbidity and mortality worldwide and pose a significant public health challenge in Indonesia. Indonesian Army (TNI AD) personnel are at risk of developing NCDs due to operational stress, smoking habits, unhealthy dietary patterns, sleep disturbances, and insufficient physical activity outside working hours. Health education is an effective health promotion strategy to improve awareness and encourage healthy lifestyle behaviors for NCD prevention. This community service program aimed to improve the knowledge of Indonesian Army personnel regarding the prevention of non-communicable diseases through health education. Methods: The program was conducted at the 18/YKR Combat Engineer Battalion, Gianyar, Bali, in August 2024 and involved 40 Indonesian Army personnel. The intervention consisted of preparation, health education delivered through lectures and interactive discussions, and evaluation using pre-test and post-test questionnaires to assess participants' knowledge before and after the educational session. Results: Before the intervention, 29 participants (72.5%) had fair knowledge and 11 (27.5%) had good knowledge regarding NCD prevention. Following the health education session, the number of participants with good knowledge increased to 14 (35.0%), while those with fair knowledge decreased to 26 (65.0%). Most participants also demonstrated improved post-test scores, indicating enhanced understanding of NCD risk factors and preventive measures. Conclusion: Health education effectively improved participants' knowledge regarding NCD prevention. Regular and sustainable educational programs in military settings are recommended to strengthen awareness, promote healthy lifestyle practices, and support the prevention of non-communicable diseases among Indonesian Army personnel.